2021
DOI: 10.1002/chem.202005246
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Photophysical Properties of a New Class of Inherently Chiral Boron(III) Chelates—The tert‐Leucine Complexes

Abstract: A new family of boron(III) chelates is introduced whereby molecular chirality, confirmed by circular dichroism, is imported during synthesis such that isolation of the diastereoisomers does not require separation procedures. The photophysical properties of two members of the family have been examined: the N,O,O‐salicylaldehyde‐based derivative shows pronounced intramolecular charge‐transfer character in fluid solution and is weakly fluorescent, with a large Stokes shift. The corresponding 2‐methylamino‐benzald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 116 publications
3
3
0
Order By: Relevance
“…To assign the correct configuration ECD spectral calculations were performed using two theoretical levels: B3LYP/6‐311++G(3df,2pd) and CAM‐B3LYP/6‐311++G(3df,2pd). As observed before, the CAM‐B3LYP functional overestimates the excitation energies by about 100 nm [14] . The ECD patterns calculated on both theoretical levels are, nevertheless, very similar (considering the mentioned excitation energy shift) and generally compare well with the experiments, apart from the vibrational signatures.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…To assign the correct configuration ECD spectral calculations were performed using two theoretical levels: B3LYP/6‐311++G(3df,2pd) and CAM‐B3LYP/6‐311++G(3df,2pd). As observed before, the CAM‐B3LYP functional overestimates the excitation energies by about 100 nm [14] . The ECD patterns calculated on both theoretical levels are, nevertheless, very similar (considering the mentioned excitation energy shift) and generally compare well with the experiments, apart from the vibrational signatures.…”
Section: Resultssupporting
confidence: 84%
“…As observed before, the CAM-B3LYP functional overestimates the excitation energies by about 100 nm. [14] The ECD patterns calculated on both theoretical levels are, nevertheless, very similar (considering the mentioned excitation energy shift) and generally compare well with the experiments, apart from the vibrational signatures. The vibrational levels could, in principle, be included in the predictions as presented by Ponce-Vargas et al, [15] but are not required for the current chiral centre assignment.…”
Section: Compoundsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, Toyota, [25][26][27] Nowak-Król [28] and others [29][30][31][32] showed that resolution of racemic mixtures of boron complexes via chiral HPLC is possible and give rise to, for example, 3 [25] or 4 [28] in enantiopure form (Schema 1b). Synthetic concepts towards enantioenriched boron atoms involve diastereoselective syntheses [30,[33][34][35][36] as in case of NHC-borane 5 [8] (Scheme 1c) or intramolecular chirality transfer towards tridentate complex 6 [37] (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“… 4 Various BODIPY analogues based on the dipyrromethene ligand have been developed to achieve the applications mentioned above, whereas the research on the development of novel luminescent boron complexes based on aromatic ligands has emerged to explore and improve the photofunctionalities. For example, some successful examples of rigid four-coordinated boron complexes based on tridentate ligands, which show unique and useful luminescent properties such as self-assembly, 5 aggregation-induced emission 6 and chiroptical properties, 7 have been reported.…”
mentioning
confidence: 99%